(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2018)
In this essay I try to underline the relation between different ways to think about the end of the world and different philosophical anthropologies, which are always presupposed in those thoughts. The article begins with an analysis of some scenes of the film Melancholia of Lars Von Trier. The explanation of those scenes is supposed to clarify my intentions and some thesis I will demonstrate in the rest of the article. I approach the problem of the relation between the end of the world and the philosophical anthropology using De Castro and Danowski’s book Is there any world to come?,and I develop their investigation by analyzing the work of Gunther Anders. I conclude the article trying to demonstrate that the problem of the Anthropocene is not the end of Life but the end of the world, and in this sense is important to conceive in a different way the man and is relation to the world.